Teachers’ opinions on kindergarten admission standards - Loudová Stralczynská, Barbora (Revija za elementarno izobraževanje, 2025)
The aim of this paper is to present the opinions of teachers on the standards for admitting toddlers to kindergartens in the Czech Republic and Slovakia, and to discuss these standards in relation to the risks to children’s well-being. Opinions were obtained through a quantitative survey among teachers from the Czech Republic (n=574) and Slovakia (n=593) in 2023. Results showed that most teachers do not support the admission of children under three to kindergartens. They conditionally support admission based on self-care skills, hygiene habits, and socioemotional independence, which do not match typical toddler development, posing pressure on the child and family.
Keywords: admission standards; child well-being; dobrobit otrok; kindergarten; merila za sprejem; Otroški vrtci; Predšolska vzgoja; pre-school teachers; toddlers; vrtec; Vzgojitelji predšolskih otrok